2008
DOI: 10.1093/bja/aen070
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of intravenous dexmedetomidine in children under 11 yr of age

Abstract: To reach a certain plasma concentration, children younger than 2 yr of age evidently need larger initial doses of dexmedetomidine than the older children, as young children have a larger volume of distribution of the drug than older children and adults. Since the total plasma clearance of dexmedetomidine is independent of age, similar rates of infusion can be used in younger and older children to maintain a steady-state concentration of dexmedetomidine in plasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 19 publications
3
65
0
1
Order By: Relevance
“…Four pharmacokinetic studies of dexmedetomidine administered to children reported values similar to those in adults: V d 1.5 --2.2 l/kg, Cl 0.56 --1 l/kg/h and t 1/2b 1.6 --2.7 h [29][30][31][32]. A pooled population pharmacokinetic analysis of the four studies cited above was best described using an allometrically-scaled twocompartment model: V d 125.3 l/70 kg (1.8 l/kg) and Cl 42.1 l/h/70 kg (0.6 l/kg/h) [33].…”
Section: Pharmacokineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four pharmacokinetic studies of dexmedetomidine administered to children reported values similar to those in adults: V d 1.5 --2.2 l/kg, Cl 0.56 --1 l/kg/h and t 1/2b 1.6 --2.7 h [29][30][31][32]. A pooled population pharmacokinetic analysis of the four studies cited above was best described using an allometrically-scaled twocompartment model: V d 125.3 l/70 kg (1.8 l/kg) and Cl 42.1 l/h/70 kg (0.6 l/kg/h) [33].…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Evaluation of the effects of dexmedetomidine on serum glucose levels shows no change in serum glucose while compared to pre-and post-infusion measurements [41]. Likewise, dexmedetomidine is not associated with an increased incidence of gastrointestinal side effects including emesis, ileus or elevated hepatic transaminase [20,21,32,38,43,65,78]. There is one case report of suspected drug fever in the adult literature [79].…”
Section: Othermentioning
confidence: 99%
“…In addition to the previously mentioned agents, dexmedetomidine (a potent, selective alpha-2 adrenoceptor agonist) may also be used. Dexmedetomidine provides natural sleep, anxiolysis and analgesia [50].…”
Section: Sedationmentioning
confidence: 99%
“…and adults to effect a steady state plasma concentration 14 . However, in patients aged ≥ 65 years, a greater incidence of hypotension and bradycardia was reported; therefore, a dose reduction in this population may be warranted 12 .…”
Section: Dexmedetomidine Is Chemically Described As (mentioning
confidence: 99%
“…However, in patients aged ≥ 65 years, a greater incidence of hypotension and bradycardia was reported; therefore, a dose reduction in this population may be warranted 12 . In children younger than 2 years of age, the volume of distribution at steady state is increased, suggesting that higher doses are required to achieve steady state; but t ½ β is prolonged, which may result in increased drug accumulation with time 14 .…”
Section: Dexmedetomidine Is Chemically Described As (mentioning
confidence: 99%